Differences in the level of workers’ motivation in repair and maintenance service enterprise in The Rail Transport - Milos Hitka; Silvia Lorincova; Martina Lipoldova; Zaneta Balazova; Denisa Debnarova (Communications - Scientific letters of the University of Zilina, 2020)
The time when the only job of a manager was to delegate work to employees is over. At the present time, an ability to motivate employees is considered an essential skill for managers. It is complex and systematic effort of a manager to create a working environment and atmosphere supporting the inner needs and interests of employees affecting their behaviour and stimulating the performance positively. Differences in the level of workers’ motivation in repair and maintenance service enterprise in the rail transport was defined using the sample set of almost 1,000 respondents and ANOVA and Duncan test. Following the results, it can be stated that the structure of motivation factors, as well as their importance, changed significantly in repair and maintenance service enterprise in the rail transport over the observation period.